Gaze of IntenCity: memories and images in André Carreira's trajectory (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This interview addresses the trajectory of director and professor André Carreira (1960), creator of the ÁHQIS Acting Laboratory (2007). It took place in 2025, in the city of Florianópolis, Santa Catarina. In this meeting, the director spoke about his childhood, his early studies, as well as the beginnings of his life in theater, revealing his artistic influences, particularly the work of the Polish director Tadeusz Kantor. In this interview, Carreira reflected on possible connections between the fields of Theater and Art Direction, taking as reference the experiences carried out at the ÁHQIS Acting Laboratory.
Keywords: ÁHQIS; André Carreira; staging; art direction; image